14n + 13c fusion cross sections and compound nucleus limitation in 27al - Di Gregorio, D. E.; Gomez del Campo, J.; Chan, Y. D.; Ford, Jr. J. L. C.; Shapira, D.; Ortiz, M. E. (American Institute of Physics, 1982)
Fil: Di Gregorio, D. E. Comisión Nacional de Energía Atómica; Argentina